2012
DOI: 10.5644/ama2006-124.50
|View full text |Cite
|
Sign up to set email alerts
|

Trace elements and cell-mediated immunity in gestational and pre-gestational diabetes mellitus at third trimester of pregnancy

Abstract: Objective. The aim of the study: To evaluate the correlations between Zn2+, Cu2+, Mg2+, Se2+ and Cr3+ and alteration in T cell subsets during diabetic and normal pregnancy. Methods. The study involved 63 women with gestational diabetes mellitus (GD) and 16 pregnant women with Type 2 diabetes and 48 healthy, non-pregnant women were included as controls. Ten ml of whole venous blood from each participant was analyzed for electrolytes by atomic absorption; total antioxidant activity, individual enzymatic antioxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 39 publications
2
19
0
Order By: Relevance
“…While IL‐4 production by T cells after mitogen stimulation was normal, IL‐2 production was reduced in diabetic mothers and in their newborns. These findings were in agreement with previous reports showing that gestational diabetes induced depressed lymphocyte proliferation and IL‐2 secretion compared to normal pregnancy . Modulation of T cell function in the presence of insulin was in agreement with our previous findings …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…While IL‐4 production by T cells after mitogen stimulation was normal, IL‐2 production was reduced in diabetic mothers and in their newborns. These findings were in agreement with previous reports showing that gestational diabetes induced depressed lymphocyte proliferation and IL‐2 secretion compared to normal pregnancy . Modulation of T cell function in the presence of insulin was in agreement with our previous findings …”
Section: Discussionsupporting
confidence: 94%
“…Serum cholesterol and triglyceride levels in diabetic pregnant women were not statistically significantly different compared to those seen in normal pregnant women . Previous studies reported a decrease in naïve T cells in diabetic pregnancy . Newborns of diabetic mothers have a reduction in NK lymphocytes than control values …”
Section: Discussionmentioning
confidence: 79%
“…T lymphocyte and its subpopulations are the most investigated cells in GDM due to its recognized role in maternal immune response. Five studies reported the percentage of total circulating TCD3 + TCD4 + , and two of them analysed the frequency of total TCD8 + as well . Friebe‐Hoffman et al found a lower frequency of TCD4 + in GDM patients compared to controls, while the others did not …”
Section: Immune Cellsmentioning
confidence: 99%
“…These parameters have been used to assess several Treg subpopulations in PB, making it difficult to compare the results of different studies. Currently, there are four papers addressing this topic, but each one has used a specific marker to characterize the Treg subset . Mahmoud et al showed increased levels of CD4 + CD25 + in GDM patients compared to controls.…”
Section: Immune Cellsmentioning
confidence: 99%
See 1 more Smart Citation